Estimation of strength indices of parts of supporting structures of traction assemblies OPE1A and prolongation of their service life - Bondaryev, O. M.; Gorobets’, V. L.; Dzichkovs’kyy, Ye. M.; Kryvchykov, O. Ye.; Yagoda, D. O.; Bondaryeva, V. S. (Science and Transport Progress, 2012)
In the article the results of a set of works directed to providing the prolongation of service life of the traction assemblies OPE1A (ОПЭ1А) are presented.